Reviving fiscal policy in Europe: towards an implementation of the golden rule of public investment - Achim Truger (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2016)
The implementation of a golden rule of public investment as a necessary institutional reform and an important step aimed at overcoming the constraints imposed by the new European Economic Governance are proposed. The rule is widely accepted in traditional public finance and can deliver both intergenerational fairness as well as more growth and employment. The golden rule would exempt public (net) investment suitably defined from the relevant deficit targets of both the preventative and the corrective arms of the Stability and Growth Pact as well as the Fiscal Compact. That way, fiscal policy would be upgraded and would receive more room for manoeuvre and public investment as a particularly growth-enhancing public expenditure category would be strengthened. Different definitions are discussed and a pragmatic definition based on the national accounts with some modifications will be proposed. The standard reservations against a golden rule are critically assessed and mostly discarded. Although a proper implementation would need some time, this should not be an excuse for not using pragmatic short-term solutions that are readily available at the European level.
Keywords: E22; E61; E62; E65; H54; H62; 330; golden rule; public investment; fiscal policy; austerity; euro area